GLAMPING RESORT DI KABUPATEN BENGKAYANG - Melza Kusfa Indriani; Emilya Kalsum; Hamdil Khaliesh (JMARS: Jurnal Mosaik Arsitektur, 2023)
The busyness that tends to be the same and the problems faced every day make people bored. You can relieve boredom by taking a vacation to natural attractions. Nature that has a varied topography such as hilly areas, beaches, valleys, and others gives rise to beautiful areas. One area that has topographic diversity is in Bengkayang Regency, West Kalimantan. One of the activities that can enjoy nature directly is camping / camping activities. Not everyone can do camping activities because the terrain is difficult to reach. Therefore, glamping (glamour camping) emerged which is a luxurious and practical camping activity as a solution. Glamping can be combined with resorts which are tourist attractions equipped with lodging facilities and produce glamping resorts that offer visitors the convenience of staying in the open. The method used is the J.C Jones method with direct data collection and based on literature studies. The aim of the design is to design a tourist area without destroying nature, to adapt to existing site conditions, and to be easy to pass. The result of the design is a tourist area that can be reached easily consisting of several masses of buildings that are placed in certain areas as facilities of the area such as glamping inns which are placed in the back area of the area and outbound which are placed scattered following the shape of the area's contours.